Workshop Proceedings On Behavioural Interventions In Dengue Control In Malaysia. - Kin, Foong (Pusat Penyelidikan Dadah dan Ubat-Ubatan Universiti Sains Malaysia, 2001)

(untitled)
The primary focus of health education programmes is to bring about behaviour change. Health professionals are discovering that changing unhealthy behaviour is difficult. However, when this is successful, the impact is extremely rewarding. The challenge therefore is to find appropriate and effective strategies that take into consideration human and environment factors that influence positive behaviours. There is sufficient evidence to show that biotechnology alone cannot prevent or control the transmission of diseases if people will not participate or change their behaviours.